Hubungan Motivasi Belajar dengan Hasil Belajar Siswa pada Pembelajaran Tematik Di Sekolah Dasar - Novianty, Dina Rahmi; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research aim to know there is or no correlation between students motivation in learning with learning outcomes in themati  learning of fourth grade of primary school on cluster two in Solok CIty. This type of research is quantitative research with correlation research methods. The amount of sample is 47 students, fourth grade of primary school on cluster two in Solok City. The result of the research there is positive correlation an significant between students motivation in learning with learning outcomes in thematic learning of fourth grade of primary school on cluster two in Solok City. This was proven from rhitung > rtabel = 0,390>0,2876, and significance value 0.000 < 0.005. Which means that Ho is rejected and Ha is accepted, so the hypothesis says "there is a correlation between students in learning motivation with learning outcomes in thematic learning in of fourth grade of primary school on cluster two in Solok City" accepted.